Studi Awal Pemodelan Aerodinamika Sayap Pesawat Tanpa Awak Kecepatan Rendah - Mulyadi Mulyadi; Tony Siagian (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2023)
This research is a prelimenary study of unmanned aerial vehicle design process. The study is conducted to understand the effect of wing shape on pressure of  the  wing  surface and to analyse air flow model on the wing surface and surround it that is crucial for the next design step.  Finite element method has been performed with the aid of computer. Computational fluid dynamics was carried out by using Freecad 0.21 software comes with powerful  OpenFOAM® Computational Fluid Dynamics workbench. Straight, tapered and tapered-bend wing shape were simulated with 1000 mm in length and constructed according to NACA 6412 profile. Straight wing had mean chord length of 100 mm while tapered wings were 80-120 mm. Furthermore, 20 m/s of wing speed was involved in simulation with angle of attack of 2 degree. Modeling results were robustly managed by means of Paraview 5.5.2 software. Results revealed that maximum surface pressure was formed on leading edge with 190 Pascals on straight wing and 210 Pascals on tapered-bend wing. Laminar air flow along wing profile was discovered without any vortex shedding occurred after passing the trail edge surface. Finally, simulation results discovered that there is a pressure difference on the top and bottom part of the wing. As the result, lifting force was created as expected.